Evidence for effective structure‐based neuromodulatory effects of new analogues of neurosteroid allopregnanolone. (18th February 2018) - Taleb, O.; Patte‐Mensah, C.; Meyer, L.; Kemmel, V.; Geoffroy, P.; Miesch, M.; Mensah‐Nyagan, A.‐G.
Abstract: The neurosteroid allopregnanolone (AP) modulates neuroendocrine/neurobiological processes, including hypothalamic‐pituitary‐adrenocortical activities, pain, anxiety, neurogenesis and neuroprotection. These observations raised the hope of developing AP‐based therapies against neuroendocrine and/or neurodegenerative disorders. However, the pleiotropic actions of AP, particularly its cell‐proliferation‐promoting effects, hamper the development of selective/targeted therapies. For example, although AP‐induced neurogenesis may serve to compensate neuronal loss in degenerative brains, AP‐evoked cell‐proliferation is contraindicated for steroid‐sensitive cancer patients. To foster progress, we synthesised 4 novel AP analogues of neurosteroids (ANS) designated BR053 (12‐oxo‐epi‐AP), BR297 (O‐allyl‐epi‐AP), BR351 (O‐allyl‐AP) and BR338 (12‐oxo‐AP). First, because AP is well‐known as allosteric modulator of GABAA receptors (GABAA‐R), we used the electrophysiological patch‐clamp technique to determine the structure‐activity relationship of our ANS on GABAA‐activated current in NCB20 cells expressing functional GABAA‐R. We found that the addition of 12‐oxo‐group did not significantly change the respective positive or negative allosteric effects of 3α‐AP or 3β‐(epi)‐AP analogues. Importantly, substitution of the 3α‐hydroxyl‐group by 3α‐O‐allyl highly modified the ANS activities. Unlike AP, BR351 induced a long‐lasting desensitisation/inhibition of GABAA‐R. Interestingly, replacement of the 3β‐hydroxyl by 3β‐O‐allyl (BR297) completely reversed the activity from negative to positive allosteric action. In a second step, we compared the actions of AP and ANS on SH‐SY5Y neuronal cell viability/proliferation using MTT‐reduction assays. Different dose‐response curves were demonstrated for AP and the ANS. By contrast to AP, BR297 was totally devoid of cell‐proliferative effect. Finally, we compared AP and ANS abilities to protect against oxidative stress‐induced neuronal death pivotally involved in neurodegenerative diseases. Both BR351 and BR297 had notable advantages over AP in protecting SH‐SY5Y cells against oxidative stress‐induced death. Thus, BR297 appears to be a potent neuroprotective compound devoid of cell‐proliferative activity. Altogether, our results suggest promising perspectives for the development of neurosteroid‐based selective and effective strategies against neuroendocrine and/or neurodegenerative disorders.